PEMBIAYAAN SYARIAH AL IJARAH MULTIJASA SEBAGAI PEMBIAYAAN PENDIDIKAN DI INDONESIA - Ashari, Muhamad Roby; Dimyati, Mochammad; Aprilliantoni, Aprilliantoni (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to find out alternative education financing that is in accordance with the sharia concept and can overcome the financing needs of students to continue higher levels of education. The presence of the fatwa of the National Sharia Council No. 44/DSN-MUI/VIII/2004 regulates how the concept of education financing based on Sharia Principles with the Al-Ijarah or kafalah method. However, education financing is included in the Al-Ijarah Multijasa category. Education financing using the Al Ijarah Multijasa method was chosen because this financing can serve a wider range of financial services, such as health financing, weddings, vehicle rental services, houses, wedding halls, building tools and other services. So that education financing is more ideal using the sharia principles of Al Ijarah Multijasa. With the presence of the fatwa of the National Sharia Council on Education financing, it is hoped that it will be able to become a financing solution so that students are free from the snares of usury that make it difficult.